2022
DOI: 10.3390/diagnostics12010220
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression Patterns of CD45RO, p105/p50, JAK3, TOX, and IL-17 in Early-Stage Mycosis Fungoides

Abstract: The morphologic changes in early-stage mycosis fungoides (MF) might overlap with benign inflammatory dermatitis (BID). Previous studies have described altered expression patterns of several proteins in MF, but their diagnostic significance is uncertain. This study aims at examining the frequency of expression of CD45RO, NFkB-p105/p50, JAK3, TOX, and IL-17 proteins by immunohistochemistry. The cohorts included 21 patients of early-stage MF and 19 with benign BID as a control group. CD45RO was positive in all pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…[12][13][14][15] However, TOX expression has been recently reported to be not specific to neoplastic T lymphocytes but also seen in reactive lymphocytes found in BIDs. [44][45][46] Consistent with the studies that challenged the original reports, TOX expression was observed in both MF and BIDs, and TOX seemed to have no diagnostic value for eMF. ) and is involved in the differentiation of naive T cells into Th1.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…[12][13][14][15] However, TOX expression has been recently reported to be not specific to neoplastic T lymphocytes but also seen in reactive lymphocytes found in BIDs. [44][45][46] Consistent with the studies that challenged the original reports, TOX expression was observed in both MF and BIDs, and TOX seemed to have no diagnostic value for eMF. ) and is involved in the differentiation of naive T cells into Th1.…”
Section: Discussionsupporting
confidence: 77%
“…The original and subsequent several studies showed that TOX expression was significantly increased in eMF, whereas it was negative or weakly increased in BIDs, and TOX was proposed as a diagnostic marker for eMF 12–15 . However, TOX expression has been recently reported to be not specific to neoplastic T lymphocytes but also seen in reactive lymphocytes found in BIDs 44–46 . Consistent with the studies that challenged the original reports, TOX expression was observed in both MF and BIDs, and TOX seemed to have no diagnostic value for eMF.…”
Section: Discussionmentioning
confidence: 84%
“…It has been hypothesised that TOX may promote the formation of exhausted T-cells akin to what happens after the stimulation of immune checkpoints such as PD-1 or CTLA-4 [ 38 , 39 ]; and it may play a role in cancer pathogenesis and progression. Some studies have evaluated TOX role in MF/SS providing contrasting results on its potential role as a diagnostic and prognostic marker [ 31 , 32 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The present study aims to evaluate TOX role of in MF/SS as a possible diagnostic marker by comparing its expression in MF/SS and in inflammatory skin diseases, and to assess whether TOX may also have a prognostic role.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, for the first time, TOX was reported to discriminate between early MF lesions and biopsies from BID 7 , however, this has not been confirmed by some later studies 8 . Other reports revealed that TOX was also expressed in infiltrating lymphocytes in BID, although the frequency of positive cells was not as high as in MF.…”
Section: Thymocyte Selection Associated High Mobility Group Box (Tox)mentioning
confidence: 91%